Mandated Sick Pay: Coverage, Utilization, and Welfare Effects - J. Catherine Maclean; Stefan Pichler; Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2020)
This paper evaluates the labor market effects of sick pay mandates in the United States. Using the National Compensation Survey and difference-in-differences models, we estimate their impact on coverage rates, sick leave use, labor costs, and non-mandated fringe benefits. Sick pay mandates increase coverage significantly by 13 percentage points from a baseline level of 66%. Newly covered employees take two additional sick days per year. We find little evidence that mandating sick pay crowds-out other non-mandated fringe benefits. We then develop a model of optimal sick pay provision along with a welfare analysis. For a range of plausible parameter values, mandating sick pay increases welfare.
Keywords: I12; I13; I18; J22; J28; J32; 330; sick pay mandates; sick leave; medical leave; employer mandates; fringe benefits; moral hazard; unintended consequences; labor costs; National Compensation Survey (NCS); welfare effects; optimal social insurance; Baily-Chetty